The Effect of Audio Visual-Based Inquiry Learning Model on Elementary Student Learning Outcomes in Science and Technology Subjects in Class IV - Kristina Sianturi, Nelli; Juliana; Janson Silaban, Patri; Lumbanraja, Bogor; Florentina Ambarwati, Nova (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study discusses the effect of the Audio Visual Media-based Inquiry learning model on the grade IV students' learning outcomes at UPT SD Negeri 068008 Damar Medan Tuntungan District in Medan in the academic year 2023/2024. The research method used is an experimental method with quantitative research. The number of research samples is 25 students based on the boring sampling technique (total sampling). The data on the Inquiry learning model was obtained from questionnaires distributed to students. Data on student learning outcomes were obtained from the students' Pretest and Post-test scores in the 2023/2024 academic year. The students' learning outcomes showed that the average score of the Pretest grade IV students was 65.12 while the Post-test average score was 88.96. Furthermore, the results of hypothesis testing showed 6,944 and 2,060. It is evident that Ho was rejected and Ha was accepted. Through the t-test, it can be concluded that there is a significant positive effect between the audio-visual media-based inquiry learning model on class IV student learning outcomes in the science and technology subject UPT SD Negeri 068008 Medan Tuntungan in the academic year 2023/2024.